2010
DOI: 10.4103/0377-4929.59178
|View full text |Cite
|
Sign up to set email alerts
|

CagA status and VacA subtypes of Helicobacter pylori in relation to histopathologic findings in Iranian population

Abstract: H. pylori strains showing vacA s1 genotype were associated with more severe gastritis. These findings show that vacA genotyping may have clinical relevance in Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 4 publications
3
7
2
Order By: Relevance
“…In four studies carried out in Iran the prevalence of s1 allele as the most common allele of VacA cytotoxin subtypes was found to be 71%, 69%, 69% and 70.5%, respectively and is in accordance with our study. [30313233] But contrary to our study, s2 allele was present in all these studies. The dominant genotype in Jafari, Dabiri and Molaei studies was vacA s1/m2, whereas in Isfahan this prevalence was 51% for vacA s1/m1 and 49% for s1/m2.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In four studies carried out in Iran the prevalence of s1 allele as the most common allele of VacA cytotoxin subtypes was found to be 71%, 69%, 69% and 70.5%, respectively and is in accordance with our study. [30313233] But contrary to our study, s2 allele was present in all these studies. The dominant genotype in Jafari, Dabiri and Molaei studies was vacA s1/m2, whereas in Isfahan this prevalence was 51% for vacA s1/m1 and 49% for s1/m2.…”
Section: Discussioncontrasting
confidence: 99%
“…These results were also reported in the previous studies carried out in Iran, Taiwan and Mexico. In the studies conducted by Yakoob, et al .,[16] Molaei, et al .,[33] Chiarini, et al .,[38] Bindayna and Mahmeed[36] significant association was found between vacA genotypes and clinical outcomes. Hussein et al .…”
Section: Discussionmentioning
confidence: 99%
“…We found that prevalence of cagA was 77.27% (17/22), which was in conformity to various studies done where the prevalence varies from 62%-77% respectively [12,13], while in one study done by Udhayakumar G et al, prevalence of cagA positive strain was 96% [14]. The prevalence of cagA genotypes in Anand district is relatively important to reveal the circulating H. pylori strains in a given geographic region and the associated need for regionspecific diagnostics for H. pylori virulence markers.…”
Section: Resultssupporting
confidence: 70%
“…While a great number of studies in Iran indicated no influence of cagA status or its 3' variable region on the progression of disease (26)(27)(28)(29)(30)(31)(32)(33)(34), correlation between positive cagA status and severe clinical outcomes was reported in some other studies (35)(36)(37). Consistent with the cases of Iranian adult populations (27,28,(38)(39)(40)(41), vacA s1 was the most prevalent in the present investigation (Table 3). This dominance was also consistent with the cases of other countries in the northern part of the Middle East (42,43).…”
Section: Discussionmentioning
confidence: 99%